HUBUNGAN PEMBERIAN SUSU FORMULA DENGAN KARIES GIGI PADA ANAK PRA SEKOLAH DI TK DAYYINAH KIDS - Sari, Endah Purwani (Jurnal Martenity and Neonatal, 2017)
Caries begins with the emergence of brown or white spots which later developed into a brown hole , this is because the food / drinks are sweet and can cause fermentation of carbohydrates , such as chocolate , candy , juice , and formula . The purpose of this study was to determine the relationship of formula feeding with dental caries in pre-school children in Nursery Kids Dayyinah Pekanbaru 2016 .This research is a quantitative research with cross sectional study design. The population in this study are all children Tk Dayyinah kids Pekanbaru the number of 161 pupils. Samples in this studywere 114 respondents using quota sampling technique. The instrument used in this study isthe checklist sheet. The analysis in this research isthe analysis of univariate and bivariate. The results showed that of the 114 respondents showed a majority univariate analysis milk formula as many as 64 people (56.1%) and a minority of 50 people (43.9%) and the majority of dental caries by 60 people (52 , 6%) and a minority of 54 people (47.4%). Results of bivariate analysis majority milk formula as many as 64 people (56.1%) and dental caries as many as 42 people (36.8%) of the Chi-square test results obtained P value P value ≤ 0.003 where in 0, 05 Hois rejected means a significantor significant relationship.